Improving Speaking Skills Through Pro-Voc Method by Students’ Self-Efficacy at Pesantren - Aisyatul Lubaba; saadatuddaroini (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study aims to increase students' feeling of being able to speak English. So the researcher tries to build students' confidence about their ability in speaking English by forming knowledge of pronunciation and vocabulary. The researcher used classroom action research with three instruments: observation, questionnaire and speaking assignment. The results showed that The PRO-VOC Method can improve students' self-efficacy in terms of speaking. There was a significant improvement in the results of the primary and final tests in the first and second cycles. The students' mean score of the primaty test was 41.36, in the first cycle it was 50.30 and 73.64 in the second cycle. Based on students' improvement in their achievement, it corresponds to their increase in feeling capable. It is proven by the results of the questionnaire that the average percentage of the student self-efficacy scale in the previous study was 46.36%, 64.55% in the first cycle and 73.37% in the second cycle